2022
DOI: 10.1371/journal.pgph.0000233
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy: Vaccination intention and attitudes of community health volunteers in Kenya

Abstract: In Kenya, community health volunteers link the formal healthcare system to urban and rural communities and advocate for and deliver healthcare interventions to community members. Therefore, understanding their views towards COVID-19 vaccination is critical to the country’s successful rollout of mass vaccination. The study aimed to determine vaccination intention and attitudes of community health volunteers and their potential effects on national COVID-19 vaccination rollout in Kenya. This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The trust in the vaccination initiative can be associated with the quicker opening of the economy and normal lifestyle. This finding is in agreement with Osur et al’s [ 6 ] study, that reported a significant association between intention to accept COVID-19 vaccines and trust in MoH (national government) decisions on COVID-19 vaccination. As of the time of writing this paper, Kenya’s government was struggling to vaccinate 10 million adult Kenyans by the end of December 2021.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The trust in the vaccination initiative can be associated with the quicker opening of the economy and normal lifestyle. This finding is in agreement with Osur et al’s [ 6 ] study, that reported a significant association between intention to accept COVID-19 vaccines and trust in MoH (national government) decisions on COVID-19 vaccination. As of the time of writing this paper, Kenya’s government was struggling to vaccinate 10 million adult Kenyans by the end of December 2021.…”
Section: Discussionsupporting
confidence: 93%
“…Inadequate resources and remunerations may hinder the CHVs from serving their clients well and especially attending to households within their areas of jurisdiction at odd hours. They need to be facilitated with resources to improve their performances and increase trust in the ministry of health messaging [ 6 ] and they need further training to enable them effectively perform their roles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase vaccine uptake, it is important to address hesitancy by identifying sources of information, perceived trustworthiness of sources and how messaging can be adapted to drive positive behaviour change. Studies have shown that individuals who report receiving COVID-19 information from social media, primarily Facebook, have the highest rates of vaccine hesitancy 6 26. An Africa CDC report found that among those surveyed in Kenya, 65% reported having seen or heard at least some misinformation about COVID-19 from social media 29.…”
Section: Introductionmentioning
confidence: 99%